Polyphenoloxidase activity and total phenolic content as related to browning of minimally processed ‘Jonagored’ apple - Rocha, Ada MCN (2011)
Phenolic content, polyphenoloxidase (PPO) activity and browning have been reported by different authors to vary in different ways, depending on cultivar, picking maturity, storage conditions, etc. Numerous authors have attempted to correlate browning results with the phenolic content and/or enzymatic activity of apples, but data published in the literature are divergent as to which of the two factors, ie the enzyme or the substrate, plays the decisive role in the overall phenomenon of enzymatic browning. The aim of this work was to follow the PPO activity and phenolic content of minimally processed apple (cv ‘Jonagored’) during cold storage and to establish a potential relationship with enzymatic browning. Increasing storage time of minimally processed apple seemed to result in an increase in PPO activity. No changes (P > 0.05) in total phenolic content were observed during storage. Colour degradation of apple cubes, as indicated by changes in colour parameters, was found to be highly correlated with PPO activity. Browning of ‘Jonagored’ apple cubes during storage was found to be moderately correlated with PPO activity. No correlation was found between the browning index and the total phenolic content.